Underwater laser communication with sloped pulse modulation in turbid water. (March 2019) - Kang, Taewoong; Kim, Kiman; Kim, Serim; Lee, Donghun
In this article, we propose the demonstration of an underwater wireless laser communication link operating at data rates of up to 100 Mbps over a band-limited turbid water channel using a modified pulse position modulation scheme with a sloped pulse. The communication link uses an avalanche photodiode module as the receiver. The bit error rate of a 5.4 × 10 −6 by 450-nm blue laser diode in turbid water with 1.4 Nephelometric Turbidity Unit was below the forward error correction limit. Our demonstrated underwater wireless laser communication system is simple to use and maintains a high data transmission rate.